Modularity and adaptive architecture – A strategy for managing complex envelope systems - Valentino Manni; Luca Saverio Valzano (Agathón)
In the face of global climate change, the built environment is experiencing an increasing demand for energy to maintain indoor comfort conditions. Inspired by systemic thinking and biomimicry, adaptive architecture can give rise to complex building organisms that dynamically respond to environmental stimuli by modulating the physicality of their envelope, thereby reducing energy consumption for climate control. Illustrating a representative framework of projects and research highlights the role of modularity in adaptive architecture in terms of operational principles, control modes, response mechanisms, functional complexity, and structural complexity. This contribution underscores the centrality of modularity as a strategy to address the multidimensional complexity of technological systems for adaptive envelopes.